Evaluation of the Impact of Fermentation Conditions, Scale Up and Stirring on Physicochemical Parameters, Antioxidant Capacity and Volatile Compounds of Green Tea Kombucha - Raniele Oliveira Alves; Rodrigo Lira de Oliveira; Marcílio Martins de Moraes; Wallysson Wagner Vilela Santos; Cláudio Augusto Gomes da Câmara; Suzana Pedroza da Silva; Camila Souza Porto; Tatiana Souza Porto (Fermentation)
This study evaluated the influence of tea, sucrose, and inoculum concentrations on green tea kombucha’s physicochemical properties and antioxidant capacity to optimize its production. The highest total phenolic content (98.61 mg GAE/100 mL) and radical scavenging activity for ABTS (9647.14 μmol/mL) and DPPH (6640.00 μmol/mL) were observed with 8 g/L of tea, 80 g/L of sucrose, and 30% inoculum. Principal Component Analysis highlighted inoculum as the key factor influencing these parameters. Following this, fermentation was scaled up in 6.5 L bioreactors operating under static and stirred conditions. Monitoring physicochemical properties, antioxidant capacity, and volatile compounds revealed the impact of agitation on fermentation, with the kombucha obtained by static cultivation presenting higher biological activity. Eleven volatile compounds were identified, including carboxylic acids, terpenes, esters, alcohols, and phenols. Notably, α-terpinolene, dodecanoic acid, and 2,4-di-tert-butylphenol, found in kombucha, exhibit antioxidant properties linked to health benefits. Differences in volatile compound profiles were observed between static and stirred processes. This study concluded that kombucha maintains its physicochemical characteristics and bioactivity during scale-up, contributing to a better understanding of large-scale production. It also suggests stirred cultivation as an alternative for kombucha production.